2016
DOI: 10.14786/flr.v4i3.236
|View full text |Cite
|
Sign up to set email alerts
|

University teachers’ perceptions of appropriate emotion display and high-quality teacher-student relationship: Similarities and differences across cultural-educational contexts

Abstract: Research on teachers' emotion display and the quality of the teacher-student relationship in higher education is increasingly significant in the context

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…Specifically, it focuses on how the affective-emotional component, and particularly personal connections and relationships between faculty and students, affect learning. Other studies have previously outlined the need for further research in this field [29, 24].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, it focuses on how the affective-emotional component, and particularly personal connections and relationships between faculty and students, affect learning. Other studies have previously outlined the need for further research in this field [29, 24].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Therefore, emotions are important in university teaching and learning processes, as an aspect which enriches the social and relational experiences underpinning student development. Research has shown that emotions and relationships are closely intertwined [29]. When students perceive that faculty listen and show immediacy through behaviors which generate a sense of closeness, they experience learning more positively, feel emotionally supported and are more likely to express their own emotions in a more authentic manner [30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following this idea, teachers' emotional experiences and expression may vary due to the cultural context, in addition to the specific teaching situation, part of which may be explicated as expression norms. Hagenauer, Glä ser-Zikuda and Volet (2016), for instance, found in interviews that Australian teacher seemed less motivated to express negative emotions in the classroom, whereas German teachers were more open about their negative emotions, especially anger, which they described as acting more on a "professional" basis. Following this study, it could be that expressing negative emotions in the questionnaire could follow different rules in these two cultural contexts: Germany and Australia.…”
Section: Studymentioning
confidence: 99%